PaCYP78A9, a Cytochrome P450, Regulates Fruit Size in Sweet Cherry (Prunus avium L.) - Qi, Xiliang; Liu, Congli; Song, Lulu; Li, Yuhong; Li, Ming (Frontiers in Plant Science, 2017)
Sweet cherry (Prunus avium L.) is an important fruit crop in which fruit size is strongly associated with commercial value; few genes associated with fruit size have, however, been identified in sweet cherry. Members of the CYP78A subfamily, a group of important cytochrome P450s, have been found to be involved in controlling seed size and development in Arabidopsis thaliana, rice, soybean, and tomato. However, the influence of CYP78A members in controlling organ size and the underlying molecular mechanisms in sweet cherry and other fruit trees remains unclear. Here, we characterized a P. avium CYP78A gene PaCYP78A9 that is thought to be involved in the regulation of fruit size and organ development using overexpression and silencing approaches. PaCYP78A9 was significantly expressed in the flowers and fruit of sweet cherry. RNAi silencing of PaCYP78A9 produced small cherry fruits and PaCYP78A9 was found to affect fruit size by mediating mesocarp cell proliferation and expansion during fruit growth and development. Overexpression of PaCYP78A9 in Arabidopsis resulted in increased silique and seed size and PaCYP78A9 was found to be highly expressed in the inﬂorescences and siliques of transgenic plants. Genes related to cell cycling and proliferation were downregulated in fruit from sweet cherry TRV::PaCYP78A9-silencing lines, suggesting that PaCYP78A9 is likely to be an important upstream regulator of cell cycle processes. Together, our ﬁndings indicate that PaCYP78A9 plays an essential role in the regulation of cherry fruit size and provide insights into the molecular basis of the mechanisms regulating traits such as fruit size in P. avium.